Liver remnant regeneration in donors after living donor liver transplantation: Long-term follow-up using CT and MR imaging - Klink, T.; Simon, P.; Knopp, C.; Ittrich, H.; Fischer, L.; Adam, G.; Koops, A. (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To assess liver remnant volume regeneration and maintenance, and complications in the long-time follow-up of donors after living donor liver transplantation using CT and MRI. Materials and Methods: 47 donors with a mean age of 33.5 years who donated liver tissue for transplantation and who were available for follow-up imaging were included in this retrospective study. Contrast-enhanced CT and MR studies were acquired for routine follow-up. Two observers evaluated pre- and postoperative images regarding anatomy and pathological findings. Volumes were manually measured on contrast-enhanced images in the portal venous phase, and potential postoperative complications were documented. Pre- and postoperative liver volumes were compared for evaluating liver remnant regeneration. Results: 47 preoperative and 89 follow-up studies covered a period of 22.4 months (range: 1 - 84). After right liver lobe (RLL) donation, the mean liver remnant volume was 522.0 ml (± 144.0; 36.1 %; n = 18), after left lateral section (LLS) donation 1,121.7 ml (± 212.8; 79.9 %; n = 24), and after left liver lobe (LLL) donation 1,181.5 ml (± 279.5; 72.0 %; n = 5). Twelve months after donation, the liver remnant volume were 87.3 % (RLL; ± 11.8; n = 11), 95.0 % (LS; ± 11.6; n = 18), and 80.1 % (LLL; ± 2.0; n = 2 LLL) of the preoperative total liver volume. Rapid initial regeneration and maintenance at 80 % of the preoperative liver volume were observed over the total follow-up period. Minor postoperative complications were found early in 4 patients. No severe or late complications or mortality occurred. Conclusion: Rapid regeneration of liver remnant volumes in all donors and volume maintenance over the long-term follow-up period of up to 84 months without severe or late complications are important observations for assessing the safety of LDLT donors. Key Points: Liver remnant volumes of LDLT donors rapidly regenerated after donation and volumes were maintained over the long-term follow-up period of up to 84 months without severe or late complications. Citation Format: • Klink T, Simon P, Knopp C et al. Liver Remnant Regeneration in Donors After Living Donor Liver Transplantation: Long-Term Follow-Up Using CT and MR Imaging. Fortschr Röntgenstr 2014; 186: 598 - 605.©Georg Thieme Verlag KG Stuttgart. New York.
CRIS-Team Scopus Importer:2024-12-04
Keywords: CT spiral; donor safety; liver; living donor liver transplantation; long-term follow-up; MR imaging